On the effect of chaotic system in performance characteristics of chaos based s-box designs - Ozkaynak, Fatih (Elsevier, 2020)
Many cryptographic protocol have been realized using similarities between chaos and cryptology. One of the most successful examples of these protocols has been s-box structures. S-box structures are a popular topic because they are the only component that provides nonlinearity property in many encryption algorithms. Therefore, in the literature, chaos based s-box designs have been proposed for almost all chaotic system classes. However, the effect of chaotic systems on these designs has not been studied in all aspects. The purpose of this study is to address this problem. It has been shown in the study that strong s-box structures can be designed by using systems that do not display chaotic behavior. This result has revealed the necessity of reexamining many designs in chaos based cryptology literature. A raw literature analysis has shown that the number of studies related to chaos based s-box designs over the last decade is more than 250. Therefore, it is thought that study outputs will bring a different perspective for chaos based cryptology literature. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Chaos; Cryptography; S-box; Effect of chaotic system